Lower medial thigh perforator (LMTP) propeller flap for reconstruction of soft tissue defects around the knee. Issue 3 (7th August 2019) - Scaglioni, Mario F.; Giunta, Gabriele; Barth, Andrè A.; Fritsche, Elmar; Arvanitakis, Michael
Abstract: Background: Skin and soft‐tissue defects around the knee are common and their reconstruction is still challenging and argued. Thin, pliable and well‐vascularized tissues are required in order to restore the aesthetic appearance of the knee and facilitate joint function. Historically local muscle flaps were employed for the upper third of the lower limb reconstruction; however, since their introduction, different perforator flaps have been proposed for this purpose. The aim of this report is to share our clinical experience with the pedicled lower medial thigh perforator (p‐LMT) flap for the reconstruction of skin and soft tissue defects around the knee. Patients and Methods: Between August 2013 and July 20, 2018, patients underwent pedicled LMT propeller flap reconstruction for defects around the knee. The subunits of the defects were the suprapatellar, the infrapatellar and patellar area and in two cases a full around the knee defect was reported. Cause of defects included trauma (13), tumor (4) and infection after knee operation (3) and defect sizes ranged from 4 × 3 cm 2 to 7 × 8 cm 2 . Results: Flap sizes ranged from 4 × 9 cm 2 to 6 × 16 cm 2 . One to two perforators based on the superficial femoral artery or descending genicular artery were found between the septum of satorius and vastus medialis, or piercing the vastus medialis during dissection. All flaps were rotated 180° in propeller fashion. All the donor sites were primarily closed and no complication at the donor site was detected. In the two cases of the total knee soft tissue defect, a double pedicled flaps reconstruction was required. After a 6 months follow‐up, all the patients in the series achieved a full range of motion. Conclusions: Fasciocutaneous flaps are currently the first reconstructive option for the soft tissue defects around the knee. The p‐LMT flap reconstruction in this case series achieved good aesthetic and functional outcomes and this flap may be a valuable option for the reconstruction of the small to medium soft tissue defects around the knee.